Characterizing the size and absorption of single nonspherical aerosol particles from angularly-resolved elastic light scattering. (February 2019) - Walters, Sequoyah; Zallie, Jason; Seymour, Gabriel; Pan, Yong-Le; Videen, Gorden; Aptowicz, Kevin B.
Highlights: Speckle size from two-dimensional angular optical scattering (TAOS) is strongly negatively correlated with cluster size of aerosol. Simulations show that analysis of two-dimensional angular optical scattering (TAOS) is able to distinguish between non-absorbing, weakly-absorbing, and strongly-absorbing single aerosol particles. Abstract: Measuring the absorption of a single aerosol particle is a challenging endeavor. Of the few techniques available, none are suitable for measuring the single-particle absorption of coarse-mode nonspherical aerosols. Analysis of two-dimensional angular optical scattering (TAOS) patterns provide a possible pathway to perform this measurement. Using a Multiple-Sphere T-Matrix (MSTM) code, we simulate the captured TAOS patterns with geometries similar to a previously designed instrument. By analyzing the size of the speckle and the integrated irradiance of these simulated TAOS patterns, we are able to distinguish between high-absorbing, weak-absorbing, and non-absorbing particles over the size range of 2 µm to 10 µm. In particular, the speckle present in the scattering patterns provides a means to estimate the size of the particle. Once the size of the particle is known, the integrated irradiance provides insight into the absorption of the particle.